KEANDALAN VALIDITY VERIFICATION SYSTEM BUKTI TRANSAKSI:MAMPUKAH MENCEGAH FRAUD ACCOUNTING? - rafles ginting; Ibnu Aswat; Helma Malini (Department of Accounting, Faculty of Economics and Business, Universitas Tadulako, 2023)
Fraud is defined as an intentional act of deception done by one or more people. This fraud can occur in management, either directly or through a third party. Many things can be done by the company in the deployment of accounting fraud prevention. One of them is confirming the validity of transaction evidence, which is critical since transaction evidence is basic transaction papers, both self-made and from third parties, that are used as sources for a company's recording or preparation of financial statements. Proof of transactions is critical in averting the creation of future financial issues. Fraud detection uses machine learning, statistical analysis, and behavioral tracking to uncover the patterns and strategies criminals use to commit fraud. When fraud is detected, the system can prevent fraud before it causes damage to your business or organization. It can be used to prove that an entity or organization has a good anti-fraud system in place.